Comprehensive identification of key compounds in different quality grades of soy sauce-aroma type baijiu by HS-SPME-GC-MS coupled with electronic nose - Wu, Junhai; Chen, Renyuan; Li, Xiaobo; Fu, Zheyang; Xian, Chun; Zhao, Wenwu; Zhao, Cheng; Wu, Xinying (Frontiers in Nutrition, 2023)
In the production of soy sauce-aroma type baijiu (SSAB), the quality of base liquor significantly affects the finished liquor’s quality. Moreover, low-quality liquor may cause health problems. The different quality grades of base liquor were analyzed to investigate the relationship between the quality and the key compounds in SSAB. In this study, samples were evaluated by the sensory and further analyzed by headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) coupled with electronic nose (E-nose). First, by sensory evaluation, the sauce, floral and fruity, fermented aromas and taste indicators (softness, fullness, harmony, purity and persistence) were positively correlated with the quality grade of the base liquor. The E-nose could distinguish the different quality grades of base liquor well. Second, differential compounds were identified via untargeted metabolome based on the HS-SPME-GC-MS. 16 common differential compounds were shared in the base liquor from different fermentation rounds, including 11 esters, 1 alcohol, 2 aldehydes and 2 ketones. It was found that the higher the quality grade of the base liquor, the richer the content of aromatics, alcohols, aldehydes and ketones. The principal component analysis (PCA) biplots of the differential compounds in the different quality grades of base liquor indicated that the superior-grade base liquor has a strong fruity aroma. By correlation analysis of the differential compounds and sensors responses of E-nose, furfuryl ethyl ether, butanoic acid ethyl ester, isopentyl hexanoate, nonanoic acid ethyl ester and 3-methyl-1-butanol had a significant effect on the response intensity of E-nose sensors. In the present study, the key differential compounds between the different quality grades of base liquor were identified, and the sensory differences between the base liquor were digitized.